Kontribusi Pemilih Pemula dalam Pesta Demokrasi Pemilu 2024 Siswa Kelas 12 TPm 3 SMK Rajasa Surabaya - Erdianto Widogo; Akhmad Qomaru Zaman (Intellektika : Jurnal Ilmiah Mahasiswa, 2024)
This study aims to analyse the contribution of novice voters in the general election, focusing on grade XII TPm 3 students. First-time voters, who have the characteristics of being critical, independent, and pro-change, play a crucial role in the success of the election. They tend to have independent views and are dissatisfied with the establishment, which makes them a group to watch out for in the democratic process. A descriptive qualitative approach was used in this study, with data collected through interviews and documentation. Data analysis was carried out systematically using triangulation techniques to ensure the validity of the findings. The results of the study show that grade XII TPm 3 students are interested in contributing to the 2024 election because they feel they have a new responsibility after obtaining an ID card and the right to vote. They see participation in the election as a new experience and an opportunity to realize their hopes and ideals in supporting their idolized leader candidates. In addition, they are driven by a desire to make positive changes, which is reflected in various forms of contribution, such as voting, witnessing elections, and providing political education to others.